SAMBAS CULTURE CENTER - Prihandono, Bowo Yuli; Lestari, Lestari; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2020)
Sambas is an area that has a variety of cultures, so it needs to be preserved in order to stay awake. The design of the Sambas Culture Center is the main alternative as a container for Sambas culture to perform, exhibit and introduce culture so that its sustainability is maintained. It is hoped that the Sambas Culture Center design will attract the interest of the community, especially the younger generation, to care about their own culture. This design method uses the J.C Jones design method. All information is analyzed, then synthesized to produce certain concepts according to the initial idea and then evaluated. This design produces a physical form and a philosophy which is a source of pride for Sambas. In this design, according to the cultural data, Sambas is most likely to be preserved, it can be divided into 3, namely in the form of performances, exhibitions, and education. The Sambas Culture Center is a single building with a triangular roof which is equipped with typical Sambas ornaments and the symbol of the Sambas Sultanate at the top of the roof.